4-Mercaptophenyldiphenylphosphine as linker to immobilize Pd onto the surface of magnetite nanoparticles. Excellent catalytic efficiency of the system after partial linker removal. Issue 111 (27th October 2015) - Guarnizo, A.; Angurell, I.; Rossell, M. D.; Llorca, J.; Muller, G.; Seco, M.; Rossell, O.
Abstract : The catalytic efficiency of Pd nanoparticles supported on Fe3 O4 NPs strongly improves after partial removal of theSdp linker. Abstract : The molecule 4-mercaptophenyldiphenylphosphine (Sdp ) has been synthesized for use as a linker to immobilize Pd nanoparticles onto the surface of magnetite nanoparticles. The high loading shown bySdp was attributed to the presence of one only anchoring (S) atom. The treatment of the resulting nanoparticles after Pd deposition with an aqueous solution of hydrogen peroxide permitted the removal of a large fraction (70%) ofSdp . Aberration corrected high-resolution scanning transmission electron microscopy images of the final nanocomposite showed that the Pd dispersion is constituted by very small nanoparticles along with a few isolated metal atoms. The partial loss of linker protection makes the Pd nanoparticles one of the most efficient catalysts for the Suzuki–Miyaura C–C cross coupling reaction and for hydrogenation of 4-nitrophenol and styrene.